2018
DOI: 10.1108/ijse-11-2017-0549
|View full text |Cite
|
Sign up to set email alerts
|

Gender and returns to entrepreneurship in Africa

Abstract: Purpose The purpose of this paper is to assess determinants of returns to male and female entrepreneurship in Ghana, Kenya and Uganda at selected quantiles along the distribution, as well as examine gender gaps in returns to entrepreneurship and factors contributing these gaps. Design/methodology/approach Employing a unique data set collected in the three countries on entrepreneurial motivations, constraints and performance, the authors apply unconditional quantile regression technique to assess the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Focussing on start-up capital, Liu et al (2019) show that women make investment choices depending on their savings behaviour, which, it should be noted, is positively associated with a competitive advantage in family firms. This finding is consistent with Agyire-Tettey et al (2018), who found that the fundamentals of a start-up’s investments influence the working capital. Some researchers discussed how working capital is the main start-up’s capital need to gain financing, investment and dividend decisions, in the long run (Motylska-Kuzma, 2017; Leitch et al , 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Focussing on start-up capital, Liu et al (2019) show that women make investment choices depending on their savings behaviour, which, it should be noted, is positively associated with a competitive advantage in family firms. This finding is consistent with Agyire-Tettey et al (2018), who found that the fundamentals of a start-up’s investments influence the working capital. Some researchers discussed how working capital is the main start-up’s capital need to gain financing, investment and dividend decisions, in the long run (Motylska-Kuzma, 2017; Leitch et al , 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Yet, evidence suggests that female entrepreneurs still have a long way to go to catch up with their male peers (Abor and Quartey, 2010). They perform significantly worse than their male counterparts, with reduced productivity (Owoo et al, 2019) and sales (Agyire-Tettey et al, 2018).…”
Section: Schaumburgmentioning
confidence: 93%
“…Thus, gender-dependent behaviour is put under question. As the most cited literature sources demonstrated there is some difference in the entrepreneur strategies of women versus men (Agyire-Tettey et al, 2018;Cañizares & García, 2010) even at the start stage while stating the decision of being the entrepreneur (Perez-Quintana et al, 2017;Solesvik et al, 2019). Women entrepreneurs are more likely to start social ventures than commercial ventures (Hechavarria & Ingram, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%